Hisperic Enigma Machine: Sea Creatures and Sources in the Hisperica Famina - Corrigan, Sarah (Peritia, 2014)
Abstract Hisperica famina texts have a coherent literary style firmly rooted in contemporary literary culture. They are not mere eccentricities. It has been convincingly argued, on the basis of form and content, that Hisperica famina may be linked to the tradition of Insular enigmata. A further level of enigma is present in the way sources are handled. Their dense complexity is at times subtended by obscure allusions to sources familiar to authors and their readers. The identification of sources gives the modern reader an encryption key that allows the arcane text to be decoded. This paper shows that parts of Pliny’s Naturalis historia are the key to allusive lines about sea creatures in Hisperica famina A and D. The paper presents new evidence for the presence of excerpts (at the least) of Pliny’s text in mid seventh-century Ireland.